2014
DOI: 10.1038/ncomms4932
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2 is critical for the maintenance of cardiac structure and function in mice

Abstract: The heart has a dynamic compensatory mechanism for haemodynamic stress. However, the molecular details of how mechanical forces are transduced in the heart are unclear. Here we show that the transient receptor potential, vanilloid family type 2 (TRPV2) cation channel is critical for the maintenance of cardiac structure and function. Within 4 days of eliminating TRPV2 from hearts of the adult mice, cardiac function declines severely, with disorganization of the intercalated discs that support mechanical couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 41 publications
3
95
0
Order By: Relevance
“…This finding is consistent with our prior murine studies where probenecid administration increased the EF in healthy mice between 5% and 8% and up to 19% in mice with reduced systolic function at baseline secondary to an induced ischemic event 18. Furthermore, this finding is also consistent with other previous reports that demonstrate that TRPV2 is a stretch‐mediated channel31, 32, 33; thus patients with markedly impaired systolic function and/or significantly dilated left ventricles may be particularly sensitive to its inotropic effects. Specifically, we found that probenecid increased contractility in most patients after a single week of therapy and that the change was more pronounced in patients with lower baseline function, though of course the clinical relevance of this change will require further studies as described below.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with our prior murine studies where probenecid administration increased the EF in healthy mice between 5% and 8% and up to 19% in mice with reduced systolic function at baseline secondary to an induced ischemic event 18. Furthermore, this finding is also consistent with other previous reports that demonstrate that TRPV2 is a stretch‐mediated channel31, 32, 33; thus patients with markedly impaired systolic function and/or significantly dilated left ventricles may be particularly sensitive to its inotropic effects. Specifically, we found that probenecid increased contractility in most patients after a single week of therapy and that the change was more pronounced in patients with lower baseline function, though of course the clinical relevance of this change will require further studies as described below.…”
Section: Discussionsupporting
confidence: 93%
“…90,91) TRPV2 is also expressed in nonneuron cells, such as pancreatic β-cells 92) and cardiomyocytes. 93) TRPV2 has been reported expressed in WAT and BAT. 56) We previously showed that TRPV2 is more highly expressed in mouse brown adipocytes than TRPV1, TRPV3, TRPV4, and TRPM8.…”
Section: Trpv2mentioning
confidence: 99%
“…These results indicate that influx of cytosolic Ca 2+ through TRPV2 affects the cardiac differentiation process and differentiated cardiomyocytes. In the murine model, cardiomyocytes isolated from TRPV2-knockout mice did not form intercalated discs and low cytosolic Ca 2+ levels were detected [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, knockdown of TRPV2 in the hearts of adult mice resulted in severe decline of cardiac function and disorganization of the intercalated discs within 4 days. After 9 days, single myocytes from TRPV2-deficient hearts showed impaired cell shortening and Ca 2+ handling [25].…”
Section: Discussionmentioning
confidence: 99%